Mosque Development as an Arena for the Contestation of Social Among Community Elites in Lombok - Azmi Maulana Fahmi (Mukaddimah: Jurnal Studi Islam, 2026)
This study examines the social dynamics and arenas of contestation among social elites in the construction of mosques in Lombok, using Pierre Bourdieu’s social capital arena theory framework. The focus of the study is on how social capital particularly symbolic capital and relational capital is utilized by various elite groups to vie for influence and legitimacy in the process of constructing mosques, which serve as symbols of identity and social power. A qualitative field research method with a case study approach was used to explore the social interactions, strategies, and conflicts occurring behind the construction of mosques in the region. The findings indicate that mosque construction is not merely a religious activity but also an arena for the contestation of social capital involving negotiation, coalition-building, and competition among social elites. This study contributes to the understanding of the relationship between social capital and local power dynamics in the context of religious social development in Lombok. Keyword: Social Capital, Social Elites, Mosque Construction.